Microparticle content of platelet concentrates is predicted by donor microparticles and is altered by production methods and stress. Issue 1 (August 2016) - Maurer-Spurej, Elisabeth; Larsen, Rune; Labrie, Audrey; Heaton, Andrew; Chipperfield, Kate
Abstract: In circulation, shedding of microparticles from a variety of viable cells can be triggered by pathological activation of inflammatory processes, by activation of coagulation or complement systems, or by physical stress. Elevated microparticle content (MPC) in donor blood might therefore indicate a clinical condition of the donor which, upon transfusion, might affect the recipient. In blood products, elevated MPC might also represent product stress. Surprisingly, the MPC in blood collected from normal blood donors is highly variable, which raises the question whether donor microparticles are present in-vivo and transfer into the final blood component, and how production methods and post-production processing might affect the MPC. We measured MPC using ThromboLUX in (a) platelet-rich plasma (PRP) of 54 apheresis donors and the corresponding apheresis products, (b) 651 apheresis and 646 pooled platelet concentrates (PCs) with plasma and 414 apheresis PCs in platelet additive solution (PAS), and (c) apheresis PCs before and after transportation, gamma irradiation, and pathogen inactivation (N = 8, 7, and 12 respectively). ThromboLUX-measured MPC in donor PRP and their corresponding apheresis PC samples were highly correlated ( r = 0.82, P = .001). The average MPC in pooled PC was slightly lower than that in apheresis PC and substantially lower in apheresis PC stored with PAS rather than plasma. Mirasol Pathogen Reduction treatment significantly increased MPC with age. Thus, MPC measured in donor samples might be a useful predictor of product stability, especially if post-production processes are necessary.